Key attributes of child psychiatry access programs - Dvir, Yael; Straus, John H.; Sarvet, Barry; Byatt, Nancy (Frontiers in Child and Adolescent Psychiatry, 2023)
The gap between the need for and the availability of pediatric mental health providers is well documented. One solution is regional/state Child Psychiatry Access Programs (CPAPs), which aid in the assessment and management of youth with behavioral health (BH) concerns by providing consultation to Pediatric Primary Care Clinicians. Our authorship team and the National Network of Child Psychiatry Access Programs (NNCPAP) board worked to describe 1) operational definitions for CPAPs elements and related outcome monitoring processes and data systems. CPAP elements include regional child psychiatry availability by phone; real time phone availability; referral and resource assistance; and, expedited face-to-face psychiatric evaluation. Defining a child psychiatry consultation program as a CPAP and describing key attributes for CPAPs is an important step in facilitating implementation of the model and advancing research into its effectiveness.